Blood parasites of Free State and Lesotho reptiles - Van As, Johann (University of the Free State, 2003)
The study of blood parasites of reptiles is a relatively new and unexplored field of research in South Africa. The Free State province and the Lesotho highlands provide a range of reptiles in which their intraerythrocytic parasite fauna were explored. Objectives of this study were to set a baseline of blood parasite diversity and to identify the enigmatic Sauroplasma Du Toit, 1937 and Serpentoplasma Pienaar, 1954 infections in lizards and snakes, respectively. Surveys were conducted in various localities in the Free State and Lesotho. Although low in diversity, 204 specimens representing 14 species of lizards, and 59 specimens representing 13 species of snakes were investigated for the presence of blood parasites. Three known infections were found: Sauroplasma thornasi Du Toit, 1937, Sauromella haemolysus Pienaar, 1954 and Hepatozoon (Haemogregarina) sebae (Laveran and Pettit, 1909) Smith, 1996. These were redescribed and S. thomasii and H. sebae were examined by aid of transmission electron microscopy. The investigation led to the discovery of six new records and possibly new species of haemogregarines named Hepatozoon sp. A-F, four new records and possibly new species of lizard malaria named Plasmodium sp. A-D, and a viral infection possibly of the Pirhemocyton type. Furthermore nine new host and distribution records for Sauroplasma in lizards and nine for Serpentoplasma in snakes are described. Ultrastructural investigations of S. thomasi in Cordylus giganteus A. Smith, 1844, Serpentoplasma in Bitis arietans arietans (Merrem, 1820) and H. sebae in Python sebae natalensis (Gmelin, 1789) were the first to examine the nature of infections in this manner. This is the first comprehensive survey of the biodiversity of blood parasites in reptiles in the Free State and Lesotho highlands.

Die studie van bloedparasiete van reptiele is 'n relatiewe nuwe en onbekende veld van navorsing in Suid Afrika. Die Vrystaat Provinsie en Lesothohooglande het 'n verskeidenheid van reptiele waarvan hul intraeretrositiese parasietfauna bestudeer was. Die doel van die studie was om 'n basislyn van bloedparasietdiversiteit op te stel, en orn die enigmatiese Sauroplasma Du Toit, 1937 en Serpentoplasma Pienaar, 1954 infeksies in akkedisse en slange onderskeidelik te identifiseer. Opnames was in verskeie lokaliteite in die Vrystaat en in Lesotho gedoen. Alhoewel laag in biodiversiteit, was 204 eksemplare, verteenwoordigend van ] 4 spesies akkedisse en 59 slange, verteenwoordigend van 13 spesies, ondersoek vir die teenwoordigheid van bloedparasiete. Drie bekende infeksies was gevind: Sauroplasma thomasi Du Toit, 1937, Sauromella haemolysus Pienaar, 1954 en Hepatozoon (Haemogregarina) sebae (Laveran and Pettit, 1909) Smith, 1996. Die material is herbeskryf en S. thomasii en H. sebae was deur middel van transmissie-elektron mikroskopie ondersoek. Die ondersoek het tot die ontdekking van ses nuwe rekords en moontlik nuwe haemogregariene spesies, naamlik Hepatozoon sp. A-F, vier nuwe rekords en moontlike nuwe spesies van akkedismalaria, naamlik Plasmodium sp. A-D, en 'n virus-infeksie wat moontlik van die Pirhemocyton tiepe is, gelei. Verder is nege nuwe gasheerverspreidingsrekords vir Sauroplasma spp. in akkedisse en nege vir Serpentoplasma spp. in slange beskryf Ultrastrukturele ondersoeke van S. thornasi in Cordylus giganteus A. Smith, 1844, Serpentoplasma sp. in Bitis arietans arietans (Merrem, 1820) en H. sebae in Python sebae natalensis (Gmelin, 1789) was die eerste keer gedoen op hierdie manier orn die aard van infeksies vas te stel. Hierdie is die eerste samevattende opname van die biodiversiteit van bloedparasiete van reptiele in die Vrystaat en Lesothohooglande.
Dissertation (M.Sc. (Zoology and Entomology))--University of the Free State, 2003
Keywords: Reptiles; Blood parasites; Haemogregarines; Lizard malaria; Sauroplasma; Serpentoplasma; Pirhemocyton; Free State; Lesotho; Squamata -- South Africa -- Free State; Squamata -- Lesotho; Blood -- Parasites